2009
DOI: 10.1007/s11695-009-9848-0
|View full text |Cite
|
Sign up to set email alerts
|

Morbid Obesity and Inflammation: A Prospective Study After Adjustable Gastric Banding Surgery

Abstract: Our results indicate that amelioration of inflammatory markers after LAGB does not seem to negatively impact nutritional status following weight reduction surgery. However, careful attention should be driven to serum IgA. Adequacy of nutritional intake and complete serial laboratory measurements should be always included in the required life-long follow-up of patients surgically treated for morbid obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Indeed WAT, but not liver Hp expression, is induced in HFD mice (46), thus establishing the tissue specificity of obesity mediated induction of Hp. Importantly, such increase is clearly associated with an enhanced inflammatory status, as demonstrated by the positive relationship found between circulating levels of Hp and those of other inflammatory markers typically induced in obesity, like CRP and TNF␣ (29) (47,76). The causal link with the latter has been detailed above.…”
Section: Circulating Hp As a Marker Of Adipositymentioning
confidence: 83%
See 1 more Smart Citation
“…Indeed WAT, but not liver Hp expression, is induced in HFD mice (46), thus establishing the tissue specificity of obesity mediated induction of Hp. Importantly, such increase is clearly associated with an enhanced inflammatory status, as demonstrated by the positive relationship found between circulating levels of Hp and those of other inflammatory markers typically induced in obesity, like CRP and TNF␣ (29) (47,76). The causal link with the latter has been detailed above.…”
Section: Circulating Hp As a Marker Of Adipositymentioning
confidence: 83%
“…Intriguingly some of the alterations indicate diminished apoptosis in the obese Hp deficient mouse liver, but whether these molecular features are reflected in a less apoptotic phenotype or if they are upstream or downstream of the protection against hepatosteatosis was not investigated. Further understanding of of Hp role in hepatosteatosis will shed light on the controversial subject of fatty liver in relation to apoptosis (76,110,111,112).…”
Section: Future Directionsmentioning
confidence: 99%
“…However, Anty and colleagues (82) reported that six months after bariatric surgery (94% gastric bypass), in a cohort of pre-menopausal women, TSAT was significantly higher (18% vs. 25%; p<0.0001). Also, several other studies have reported no significant change in iron status following gastric bypass or gastric banding surgery (8385) While another study reported a significant decrease in sTfR concentrations at 18 months post-surgery (baseline: 1.40 vs. follow-up 1.27 mg/l; p <0.05) suggesting improvement in iron status (86). …”
Section: Obesity: Iron Status Absorption Hepcidin Ex Pression and mentioning
confidence: 99%
“…As mentioned above, the restrictive bariatric interventions AGB and sleeve gastrectomy improved functional iron status as indicated by a decrease in hepcidin and an increase in transferrin saturation [44]. Nonetheless, improvement in functional iron status was reported along with weight reduction after restrictive procedures, whereas after malabsorptive procedures, worsening of ID or at least persistence is frequently observed [60,61]. …”
Section: Bariatric Surgery and Iron Deficiencymentioning
confidence: 99%